FUNGSI DAN NILAI MANTRA DALAM MASYARAKAT BANJAR - Purwanti, Purwanti; Wahyuni, Ian (Fakultas Ilmu Budaya, Universitas Mulawarman, 2020)
This study focuses on oral traditions that contain local wisdom. Mantra is an oral tradition that lives and develops in a society, especially in Banjar society. This study aims to discover the functions and values of the mantra that exist in the Banjar community. This research is a library research that uses a descriptive qualitative approach. The research data were obtained through the book collection